Implementation of Breathing Exercises at Home in Hypertension Patients in Adults Aged 36-45 Years - Ola, Fransiska Keron (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
Hypertension is one of the diseases of the cardiovascular system that has high mortality and morbidity rates. High blood pressure in hypertensive patients can be treated with pharmacological and non-pharmacological therapy. One of the non-pharmacological therapies is deep breathing relaxation therapy. This study aims to determine the effectiveness of deep breathing relaxation therapy on reducing blood pressure in patients with hypertension. The sample in this study were patients with hypertension in Kelurahan Jawa, RT 19 and RT 26 Samarinda as many as 40 respondents. The design of this study was to use a Cluster-randomized trial design by conducting a cluster randomized controlled trial with a 1:1 community-based intervention and control group. The results of the study above show that the systolic blood pressure value before being given deep breathing relaxation therapy was 160.451 mmHg and the systolic blood pressure after being given deep breathing therapy was 130 mmHg. And the diastolic blood pressure before being given deep breathing therapy was 98 mmHg and the diastolic blood pressure after being given deep breathing therapy was 84.35 mmHg. In this study, the confidence level taken was 95% with 5% (0.05). Based on statistical analysis using paired sample T-test, the systolic blood pressure value was 0.001. This means that the value is smaller than 5% (0.05) so that H0 is rejected, which means that there is an effect of deep breathing relaxation therapy on reducing blood pressure in people with hypertension. The average systolic blood pressure value after being given deep breathing relaxation therapy was 30.46 mmHg and the average diastolic blood pressure after being given deep breathing relaxation therapy was 84.35 mmHg. There was a decrease in the respondents' blood pressure after being given deep breathing relaxation therapy, namely systolic blood pressure of 130 mmHg and diastolic blood pressure of 84.35 mmHg. Based on statistical analysis using paired sample T-test with a confidence level taken at 95% with 5% (0.05), the diastolic blood pressure value was 0.001 and the diastolic blood pressure value was 0.001. This shows that deep breathing relaxation therapy is effective in lowering blood pressure in hypertensive patients. This study recommends that deep breathing relaxation therapy is effective in lowering blood pressure (systolic and diastolic) in hypertensive patients.